(3fRgI GdfOjes - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3QCjJ ai JQLeI GHf CHj WGgQ WjahQ GdeQhPi Cfg Ufa cJGHG ai GdGYJPGQ ef XQWI hgH hde Cba Ydjg EdG Cfi QCjJ QSGdI ai Pdc efShHI Edi hgH faSg aQCjJ Cf CdNUgG s
(3BNQgG (B:s
(3GfJgi hdg GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: 19s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfS HJGQjN (B1256 (3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1949s
Keywords: (3GdCOHs